Wprowadzenie funkcji użyteczności jako jednego z pojęć podstaw teorii ubezpieczeń - Obidziński, Piotr (Introducing of Utility Function as Fundamental Idea of Insurance Theory, 2006)
In this article author presents the way of introducing utility function at exercises on "Basis of Insurance Theory" subject. Author propose his own idea of gamble leading to construct utility function in different situations defined by capital and risk. Except construct utility function author presents the measure of inclination to risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 136-143